Preparation method of super-hydrophobic fluoroplastic pipeline
By synthesizing a combination of high-strength polymers with fluoroplastic and nanosilicon dioxide, a fluoroplastic pipeline with a large number of continuous benzene rings and ether bonds with superhydrophobicity and wear resistance is prepared, which solves the problem of fluoroplastic pipelines at high flow rates or high Wear problems under particulate conditions, fluoroplastic pipes with long life and efficient hydrophobic properties have been achieved.
Patent Information
- Application Number
- CN202411750436.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing fluoroplastic pipelines are prone to wear when transporting high flow rates or high particulate content media, resulting in a degradation of hydrophobic performance. The wear chips and debris generated by the wear may block the hydrophobic channel, affecting its superhydrophobic effect.
A preparation method is adopted to synthesize high-strength polymers through Friedel-Crafts acylation reaction and Mannich reaction, and mix them with fluoroplastic particles and nanosilica, and then soak them in polydimethylsiloxane solution after high temperature firing. A superhydrophobic fluoroplastic pipe with tensile resistance and friction resistance is formed.
It improves the wear resistance and hydrophobic properties of fluoroplastic pipes, extends the service life, and forms a gas isolation layer through the silane outer film, maintains superhydrophobicity, and the preparation method is simple and easy to control, suitable for large-scale industrial production.
Smart Images

Figure CN119192644A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a method for preparing a super-hydrophobic fluoroplastic pipe. Background Art
[0002] Superhydrophobicity is manifested by the water droplets being spherical on the solid surface, with a contact angle greater than 150 degrees and a rolling angle less than 10 degrees. The realization of this property mainly depends on two factors: the low surface energy of the material surface and the microscopic roughness of the surface. When the low surface energy material has a microscopic roughness, an air film will form between the water droplets and the material, hindering the wetting of the material surface by water, thus forming a superhydrophobic state.
[0003] In the prior art, fluoroplastics are relatively soft and are easily worn or scratched, especially in media conveying high flow rates or high particle content. The wear of the fluoroplastic surface will cause changes in its original microstructure and morphology. These microstructures, such as micro-nanoscale protrusions and depressions, are essential for maintaining the hydrophobic properties of fluoroplastics. Wear will destroy these structures, making the surface relatively flat, thereby reducing its hydrophobic properties. Secondly, wear may produce abrasive chips and debris, which may adhere to the surface of fluoroplastics, further affecting its hydrophobic properties. Abrasive chips and debris may block the original hydrophobic channels, making it difficult for water droplets to form a continuous contact angle on the surface, thereby reducing its hydrophobic effect. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a super-hydrophobic fluoroplastic pipe, so as to solve the problems mentioned in the above background technology.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a super-hydrophobic fluoroplastic pipe comprises the following steps: Step 1: Mix p-fluorobenzoyl chloride, m-fluorobenzaldehyde and anhydrous aluminum chloride in a stainless steel reactor, raise the system temperature to 160-180°C under nitrogen protection, and then react at 160-180°C for 16-24 hours. After the reaction, wash the reaction solution with a 10% hydrochloric acid solution and separate the organic layer with a separatory funnel. The organic layer is rotary evaporated to obtain intermediate 1; wherein the purity of the catalyst anhydrous aluminum chloride is 99.9%; Step 2: Mix the intermediate 1, 3-aminopropyltriethoxysilane, acetone, proline and dimethyl sulfoxide in a container, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 40-60°C for 4-6 hours. After the reaction is completed, remove the solvent by rotary evaporation, and wash the remaining solid with a saturated sodium carbonate solution and dry to obtain the intermediate 2; Step 3: Mix the intermediate 2, bisphenol AF, potassium carbonate, xylene and diphenyl sulfone in a container, install a condenser and a thermometer, start magnetic stirring, raise the system temperature to 300-340°C under nitrogen protection, and then react at 300-340°C for 3-4 hours. After the reaction is completed, cool it in an ice water bath, crush the obtained solid, wash it repeatedly with a hot acetone solution and dry it to obtain a high-strength polymer; wherein the hot acetone solution used in the post-treatment is a 30% by mass acetone aqueous solution, and the temperature range is 40-50°C; Step 4: Mix the fluoroplastic particles, the high-strength polymer obtained in the third step, and nano-silicon dioxide, and grind and crush them to obtain a prefabricated mixture; Step 5: The prefabricated mixture obtained in the fourth step is fired at high temperature, stirred, poured into a mold, and cooled to obtain a fluoroplastic pipe; Step 6: Soak the fluoroplastic pipe obtained in the fifth step in a polydimethylsiloxane solution, then take it out and dry it to obtain a super-hydrophobic fluoroplastic pipe.
[0006] Furthermore, the dosage ratio of p-fluorobenzoyl chloride, m-fluorobenzaldehyde and anhydrous aluminum chloride used in the first step is 0.1 mol: 0.1 mol: 24-30 g.
[0007] Furthermore, the usage ratio of the intermediate 1, 3-aminopropyltriethoxysilane, acetone, proline and dimethyl sulfoxide used in the second step is 0.08 mol: 0.08 mol: 0.1 mol: 0.003-0.004 mol: 60-80 mL.
[0008] Furthermore, the usage ratio of the intermediate 2, bisphenol AF, potassium carbonate, xylene and diphenyl sulfone used in the third step is 0.05 mol: 0.05 mol: 7-10 g: 40-60 mL: 60-80 g.
[0009] Furthermore, the fluoroplastic particles in the fourth step are polytetrafluoroethylene particles, and the mass ratio of the fluoroplastic particles in the fourth step, the high-strength polymer obtained in the third step, and nano-silicon dioxide is 90-97:3-10:2-4.
[0010] Furthermore, the particle size specification of the nano-silicon dioxide in the fourth step is 15-30nm.
[0011] Furthermore, the firing temperature in the fifth step is 330-360°C.
[0012] Furthermore, the stirring speed in the fifth step is 150-200 r / min.
[0013] Furthermore, the polydimethylsiloxane solution in the sixth step is a n-hexane solution of polydimethylsiloxane with a mass fraction of 4-5%.
[0014] Furthermore, the drying temperature in the sixth step is 60° C., and the soaking time is 60 s.
[0015] Beneficial effects of the present invention: (1) The present invention uses p-fluorobenzoyl chloride and m-fluorobenzaldehyde as raw materials, and undergoes Friedel-Crafts acylation reaction under the condition of anhydrous aluminum chloride as a catalyst to obtain intermediate 1, and then uses intermediate 1, 3-aminopropyltriethoxysilane and acetone as raw materials, and undergoes Mannich reaction under the condition of proline as a catalyst to obtain intermediate 2. Finally, uses intermediate 2 and bisphenol AF as raw materials, and undergoes nucleophilic substitution polymerization under the condition of potassium carbonate as a catalyst to obtain a high-strength polymer. The high-strength polymer structure of the present invention contains a large number of carbon-fluorine bonds and has good compatibility with the fluoroplastic substrate. In addition, the high-strength polymer structure of the present invention contains a large number of continuous and tight benzene rings and ether bonds, and the molecules are arranged in an orderly manner, so it has good tensile resistance and friction resistance. In addition, the high-strength polymer of the present invention also has an organic silicon structure, which has good weather resistance and can also improve the bonding force between the fluoroplastic pipe and the silane outer film, thereby improving the service life of the super-hydrophobic pipe.
[0016] (2) The present invention uses self-made high-strength polymer, fluoroplastic particles and nano-silica as raw materials to prepare a super-hydrophobic fluoroplastic pipe. The present invention prepares a high-strength polymer first, grinds and crushes the high-strength polymer and fluoroplastic particles with nano-silica to prepare a prefabricated mixture, and then melts the prefabricated mixture at high temperature, stirs it evenly and pours it into a mold for cooling to prepare a fluoroplastic pipe. Finally, the fluoroplastic pipe is immersed in a polydimethylsiloxane solution and then dried and coated to obtain a super-hydrophobic fluoroplastic pipe. The present invention improves the wear resistance of the fluoroplastic pipe by blending and modifying the fluoroplastic with a self-made high-strength polymer, so that when the fluoroplastic is used to transport a medium with a high flow rate or a high particle content, its wear resistance is improved, thereby being able to exhibit super-hydrophobicity. The surface of the prepared fluoroplastic pipe is attached with a rough silane outer film, which not only plays an outer protective role for the fluoroplastic pipe, but also forms a gas isolation layer between the outer film and water droplets when water molecules pass through, so that the water droplets cannot contact the surface of the outer film, thereby exhibiting super-hydrophobicity.
[0017] (3) The preparation method of the present invention has low production difficulty, and various parameter conditions are easy to control, which is conducive to large-scale industrial production. The prepared super-hydrophobic fluoroplastic pipe has good hydrophobic performance, long service life, and good friction resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The present invention will be further described below in conjunction with the accompanying drawings.
[0019] Figure 1 This is an infrared spectrum test chart of the high-strength polymer prepared by the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0021] A high-strength composite material comprises the following preparation steps: Step 1: 0.1 mol of p-fluorobenzoyl chloride, 0.1 mol of m-fluorobenzaldehyde, and 24 g of anhydrous aluminum chloride with a purity of 99.9% were mixed in a reaction container, the system temperature was raised to 160°C under nitrogen protection, and then the reaction was carried out at 160°C for 24 hours. After the reaction was completed, the reaction solution was acid-washed with a 10% mass fraction dilute hydrochloric acid solution and the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 1; Step 2: 0.08 mol of intermediate 1, 0.08 mol of 3-aminopropyltriethoxysilane, 0.1 mol of acetone, 0.003 mol of proline, and 60 mL of dimethyl sulfoxide were mixed in a container, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 40°C for 6 hours. After the reaction was completed, the solvent was removed by rotary evaporation, and the remaining solid was washed with a saturated sodium carbonate solution and dried to obtain intermediate 2; Step 3: Mix 0.05 mol of intermediate 2, 0.05 mol of bisphenol AF, 7 g of potassium carbonate, 40 mL of xylene and 60 g of diphenyl sulfone in a container, install a condenser and a thermometer, turn on the magnetic stirring, raise the system temperature to 300 °C under nitrogen protection, and then react at 300 °C for 4 hours. After the reaction is completed, cool it in an ice water bath, crush the obtained solid, wash it repeatedly with a 30% by mass acetone aqueous solution at a temperature of 40 °C and dry it to obtain a high-strength polymer. Example 2
[0022] A high-strength composite material comprises the following preparation steps: Step 1: 0.1 mol of p-fluorobenzoyl chloride, 0.1 mol of m-fluorobenzaldehyde, and 27 g of anhydrous aluminum chloride with a purity of 99.9% were mixed in a reaction container, the system temperature was raised to 170°C under nitrogen protection, and then the reaction was carried out at 170°C for 20 hours. After the reaction was completed, the reaction solution was acid-washed with a 10% mass fraction dilute hydrochloric acid solution and the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 1; Step 2: 0.08 mol of intermediate 1, 0.08 mol of 3-aminopropyltriethoxysilane, 0.1 mol of acetone, 0.0035 mol of proline, and 70 mL of dimethyl sulfoxide were mixed in a container, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 50°C for 5 hours. After the reaction was completed, the solvent was removed by rotary evaporation, and the remaining solid was washed with a saturated sodium carbonate solution and dried to obtain intermediate 2; Step 3: Mix 0.05 mol of intermediate 2, 0.05 mol of bisphenol AF, 8.5 g of potassium carbonate, 50 mL of xylene and 70 g of diphenyl sulfone in a container, install a condenser and a thermometer, turn on the magnetic stirring, raise the system temperature to 320°C under nitrogen protection, and then react at 320°C for 3.5 hours. After the reaction is completed, cool it in an ice water bath, crush the obtained solid, wash it repeatedly with a 45°C 30% mass fraction acetone aqueous solution and dry it to obtain a high-strength polymer. Example 3
[0023] A high-strength composite material comprises the following preparation steps: Step 1: 0.1 mol of p-fluorobenzoyl chloride, 0.1 mol of m-fluorobenzaldehyde, and 30 g of anhydrous aluminum chloride with a purity of 99.9% were mixed in a reaction container, the system temperature was raised to 180°C under nitrogen protection, and then the reaction was carried out at 180°C for 16 hours. After the reaction was completed, the reaction solution was acid-washed with a 10% mass fraction dilute hydrochloric acid solution and the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 1; Step 2: 0.08 mol of intermediate 1, 0.08 mol of 3-aminopropyltriethoxysilane, 0.1 mol of acetone, 0.004 mol of proline, and 80 mL of dimethyl sulfoxide were mixed in a container, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 60°C for 4 hours. After the reaction was completed, the solvent was removed by rotary evaporation, and the remaining solid was washed with a saturated sodium carbonate solution and dried to obtain intermediate 2; Step 3: Mix 0.05 mol of intermediate 2, 0.05 mol of bisphenol AF, 10 g of potassium carbonate, 60 mL of xylene and 80 g of diphenyl sulfone in a container, install a condenser and a thermometer, turn on the magnetic stirring, raise the system temperature to 340°C under nitrogen protection, and then react at 340°C for 3 hours. After the reaction is completed, cool it in an ice water bath, crush the obtained solid, wash it repeatedly with a 30% mass fraction acetone aqueous solution at a temperature of 50°C and dry it to obtain a high-strength polymer. Example 4
[0024] A method for preparing a super-hydrophobic fluoroplastic pipe comprises the following steps: The first step: polytetrafluoroethylene particles, the high-strength polymer obtained in Example 1, and nano-silicon dioxide are mixed and ground to obtain a prefabricated mixture, wherein the nano-silicon dioxide used in this step has a particle size of 15 nm, and the mass ratio of the fluoroplastic particles, the high-strength polymer obtained in Example 1, and the nano-silicon dioxide in this step is 900 g: 30 g: 20 g; Step 2: The prefabricated mixture obtained in the first step is fired at a temperature of 330°C and stirred at a speed of 150r / min, and then poured into a mold for cooling to obtain a fluoroplastic pipe; Step 3: Soak the fluoroplastic pipe obtained in the second step in a 4% by mass polydimethylsiloxane n-hexane solution for 60 seconds, then take it out and dry it at 60°C to obtain a super-hydrophobic fluoroplastic pipe. Example 5
[0025] A method for preparing a super-hydrophobic fluoroplastic pipe comprises the following steps: Step 1: Mix polytetrafluoroethylene particles, the high-strength polymer obtained in Example 2, and nano-silicon dioxide, and grind and crush to obtain a prefabricated mixture, wherein the nano-silicon dioxide used in this step has a particle size of 30 nm, and the mass ratio of the fluoroplastic particles, the high-strength polymer obtained in Example 2, and the nano-silicon dioxide in this step is 940 g: 60 g: 30 g; Step 2: The prefabricated mixture obtained in the first step is fired at a temperature of 345°C and stirred at a speed of 175r / min, and then poured into a mold for cooling to obtain a fluoroplastic pipe; Step 3: Soak the fluoroplastic pipe obtained in the second step in a 4.5% by mass polydimethylsiloxane n-hexane solution for 60 seconds, then take it out and dry it at 60°C to obtain a super-hydrophobic fluoroplastic pipe. Example 6
[0026] A method for preparing a super-hydrophobic fluoroplastic pipe comprises the following steps: The first step: polytetrafluoroethylene particles, the high-strength polymer obtained in Example 3, and nano-silicon dioxide are mixed and ground to obtain a prefabricated mixture, wherein the nano-silicon dioxide used in this step has a particle size of 15 nm, and the mass ratio of the fluoroplastic particles, the high-strength polymer obtained in Example 1, and the nano-silicon dioxide in this step is 970 g: 100 g: 40 g; Step 2: The prefabricated mixture obtained in the first step is fired at a temperature of 360°C and stirred at a speed of 200r / min, and then poured into a mold for cooling to obtain a fluoroplastic pipe; Step 3: Soak the fluoroplastic pipe obtained in the second step in a 5% by mass polydimethylsiloxane n-hexane solution for 60 seconds, then take it out and dry it at 60°C to obtain a super-hydrophobic fluoroplastic pipe.
[0027] Analysis example 1 The high-strength polymer prepared in Example 1 was analyzed by infrared spectroscopy using a Nicolet 6700 Fourier transform infrared spectrometer produced by Thermo Corporation of the United States. Figure 1 As shown, in the infrared spectrum of high-strength polymers, The carbon-fluorine bond absorption peak appears. Ether bond absorption peak appears at The carbon-silicon bond absorption peak of organic silicon appears. The carbonyl absorption peak is The benzene ring absorption peak appears. Secondary amine absorption peak appears.
[0028] Comparative Example 1 A method for preparing a super-hydrophobic fluoroplastic pipe comprises the following steps: The first step: grinding and crushing 900g of polytetrafluoroethylene particles to obtain a pre-mixed material; Step 2: The prefabricated mixture obtained in the first step is fired at a temperature of 339°C and stirred at a speed of 182r / min, and then poured into a mold for cooling to obtain a fluoroplastic pipe.
[0029] Comparative Example 2 A method for preparing a super-hydrophobic fluoroplastic pipe comprises the following steps: The first step: mixing polytetrafluoroethylene particles and nano-silicon dioxide and grinding and crushing to prepare a pre-mixed material, wherein the nano-silicon dioxide used in this step has a particle size of 30 nm, and the mass ratio of the fluoroplastic particles and the nano-silicon dioxide in this embodiment in this step is 900 g:20 g; Step 2: The prefabricated mixture obtained in the second step is fired at a temperature of 339°C and stirred at a speed of 182r / min, and then poured into a mold for cooling to obtain a fluoroplastic pipe.
[0030] Comparative Example 3 A method for preparing a super-hydrophobic fluoroplastic pipe comprises the following steps: Step 1: Mix polytetrafluoroethylene particles and nano-silicon dioxide and grind them to obtain a pre-mixed material, wherein the nano-silicon dioxide used in this step has a particle size of 30 nm, and the mass ratio of fluoroplastic particles to nano-silicon dioxide in this step is 940 g:30 g; Step 2: The prefabricated mixture obtained in the first step is fired at a temperature of 339°C and stirred at a speed of 182r / min, and then poured into a mold for cooling to obtain a fluoroplastic pipe; Step 3: Soak the fluoroplastic pipe obtained in the second step in a 5% by mass polydimethylsiloxane n-hexane solution for 60 seconds, then take it out and dry it at 60°C to obtain a super-hydrophobic fluoroplastic pipe.
[0031] Comparative Example 4 This comparative example is a polytetrafluoroethylene tube sold by Shenzhen Dankai Technology Co., Ltd.
[0032] The super-hydrophobic fluoroplastic pipes of Examples 4-6 and Comparative Examples 1-3 and the polytetrafluoroethylene pipe of Comparative Example 4 were tested for water contact angle using a JC2000C1 optical contact angle meter at room temperature, and the compressive strength test was performed in accordance with the national standard GB / T1039-1992, and the friction resistance test was performed in accordance with GB / T3960-2016. The test results are shown in Table 1: Table 1 ; It can be seen from Table 1 that the water contact angles of the super-hydrophobic fluoroplastic pipes of the present invention in Examples 4-6 are all greater than 150°, reaching the super-hydrophobic standard, and the compressive strength and friction resistance are better than those of commercially available polytetrafluoroethylene pipes. In Comparative Examples 1-3, the effects of other raw materials of the present invention on the properties of fluoroplastic pipes are demonstrated in turn through control experiments. The nano-silicon dioxide in the raw materials can enhance the friction resistance of the fluoroplastic pipes. The hydrophobicity of the fluoroplastics can be effectively improved by attaching a silane outer film on the surface by soaking in a polydimethylsiloxane solution. The high-strength polymer in the raw materials can enhance the bonding force between the fluoroplastic pipe and the silane outer film, further enhance the hydrophobicity of the fluoroplastic pipe, and enhance the compressive strength of the fluoroplastic pipe. In summary, the super-hydrophobic fluoroplastic pipe prepared by the preparation method of the present invention can meet the super-hydrophobic standard, has good hydrophobicity, and has excellent compressive strength and friction resistance. The preparation method is simple, the parameters are easy to control, and it is conducive to large-scale industrial production.
[0033] The above is a detailed introduction to the preparation method of a super-hydrophobic fluoroplastic pipe provided by the present invention. The principle and implementation method of the present invention are described in detail using specific examples herein. The description of the above embodiments is only used to help understand the method of the present invention and its core idea, including the best mode, and also enables any technician in the field to practice the present invention, including manufacturing and using any device or system, and implementing any combination method. It should be pointed out that for ordinary technicians in the technical field, the present invention can also be improved and modified without departing from the principle of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention can be used in combination with each other in any way. The fact that these combinations are not exhaustively described in this specification is only for the consideration of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing a super-hydrophobic fluoroplastic pipe, characterized in that: The following steps are involved: Step 1: Mix p-fluorobenzoyl chloride, m-fluorobenzaldehyde and anhydrous aluminum chloride in a container, raise the system temperature to 160-180° C. under nitrogen protection, and then react at 160-180° C. for 16-24 hours to obtain intermediate 1; Step 2: Mix the intermediate 1, 3-aminopropyltriethoxysilane, acetone, proline and dimethyl sulfoxide in a container, stir evenly, and react at a temperature of 40-60° C. for 4-6 hours to obtain the intermediate 2; Step 3: Mix the intermediate 2, bisphenol AF, potassium carbonate, xylene and diphenyl sulfone in a container, stir evenly, raise the system temperature to 300-340°C under nitrogen protection, and then react at 300-340°C for 3-4h to obtain a high-strength polymer; Step 4: Mix the fluoroplastic particles, the high-strength polymer obtained in the third step, and nano-silicon dioxide, and grind and crush them to obtain a prefabricated mixture; Step 5: The prefabricated mixture obtained in the fourth step is fired at high temperature, stirred, poured into a mold, and cooled to obtain a fluoroplastic pipe; Step 6: Soak the fluoroplastic pipe obtained in the fifth step in a polydimethylsiloxane solution, then take it out and dry it to obtain a super-hydrophobic fluoroplastic pipe.
2. The method for preparing a super-hydrophobic fluoroplastic pipe according to claim 1, characterized in that: The purity of the anhydrous aluminum chloride used in the first step is 99.99%, and the amount ratio of p-fluorobenzoyl chloride, m-fluorobenzaldehyde and anhydrous aluminum chloride used is 0.1 mol: 0.1 mol: 24-30 g.
3. The method for preparing a super-hydrophobic fluoroplastic pipe according to claim 1, characterized in that: The amount ratio of the intermediate 1, 3-aminopropyltriethoxysilane, acetone, proline and dimethyl sulfoxide used in the second step is 0.08 mol: 0.08 mol: 0.1 mol: 0.003-0.004 mol: 60-80 mL.
4. The method for preparing a super-hydrophobic fluoroplastic pipe according to claim 1, characterized in that: The usage ratio of the intermediate 2, bisphenol AF, potassium carbonate, xylene and diphenyl sulfone used in the third step is 0.05 mol: 0.05 mol: 7-10 g: 40-60 mL: 60-80 g.
5. The method for preparing a super-hydrophobic fluoroplastic pipe according to claim 1, characterized in that: The fluoroplastic particles in the fourth step are polytetrafluoroethylene particles, and the mass ratio of the fluoroplastic particles, the high-strength polymer obtained in the third step, and nano-silicon dioxide is 90-97:3-10:2-4.
6. The method for preparing a super-hydrophobic fluoroplastic pipe according to claim 1, characterized in that: The particle size specification of the nano-silicon dioxide in the fourth step is 15-30nm.
7. The method for preparing a super-hydrophobic fluoroplastic pipe according to claim 1, characterized in that: The firing temperature in the fifth step is 330-360°C.
8. The method for preparing a super-hydrophobic fluoroplastic pipe according to claim 1, characterized in that: The stirring speed condition in the fifth step is 150-200r / min.
9. The method for preparing a super-hydrophobic fluoroplastic pipe according to claim 1, characterized in that: The polydimethylsiloxane solution in the sixth step is a n-hexane solution of polydimethylsiloxane with a mass fraction of 4-5%.
10. The method for preparing a super-hydrophobic fluoroplastic pipe according to claim 1, characterized in that: The sixth step is drying at 60°C and soaking for 60 seconds.
Citation Information
Patent Citations
Durable super-hydrophilic or super-hydrophobic plastic surface and preparation method thereof
CN109251345A
Pollution-resistant polyethersulfone ultrafiltration membrane
CN115646223A
Preparation method of radiation refrigeration coating with super-hydrophobic performance
CN116102928A
Wear-resistant super-hydrophobic nano composite coating and preparation method thereof
CN116179047A
New fluorobisphenol compound and its production
JP1994135875A
